Comprehensive survey of UAVs communication networks (2020)
Recently, technologies related to Unmanned Aerial Vehicle (UAV) are growing rapidly particularly sensors, networking, and processing technologies. Accordingly, governments and industry have heavily invested in the studies of UAVs and improvingtheir performances for reliable and secure deployments. The design methods and the investigation of UAVs systems have progressed from mono-UAV uses to multi-UAVs and cooperative UAVs systems that need a high level of coordination and collaboration to perform tasks which require new networking models, approaches, and mechanisms for highly mobile nodes involving many complex parameters and constraints. In this context, this paper provides more details and offers a thorough investigation concerning UAV communication protocols, networking systems, architectures, and applications. In addition, we discuss UAV solutions as well as highlighting important technical challenges and open research issues requiring further studies and R&D work.